2018
DOI: 10.3390/s18092966
|View full text |Cite
|
Sign up to set email alerts
|

A Device-Independent Efficient Actigraphy Signal-Encoding System for Applications in Monitoring Daily Human Activities and Health

Abstract: Actigraphs for personalized health and fitness monitoring is a trending niche market and fit aptly in the Internet of Medical Things (IoMT) paradigm. Conventionally, actigraphy is acquired and digitized using standard low pass filtering and quantization techniques. High sampling frequencies and quantization resolution of various actigraphs can lead to memory leakage and unwanted battery usage. Our systematic investigation on different types of actigraphy signals yields that lower levels of quantization are suf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(55 citation statements)
references
References 37 publications
0
55
0
Order By: Relevance
“…Figure 1.2 illustrates the overall structure of an IoT model. Figure 1.2: IoT -The Big Picture [10] In order to understand the IoT framework, two main aspects of this internet-connectivity model along with the functioning of its layered have been covered. Figure 1.3 depicts two aspects of the IoT architecture, namely -hardware and software.…”
Section: Internet Of Things (Iot)mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1.2 illustrates the overall structure of an IoT model. Figure 1.2: IoT -The Big Picture [10] In order to understand the IoT framework, two main aspects of this internet-connectivity model along with the functioning of its layered have been covered. Figure 1.3 depicts two aspects of the IoT architecture, namely -hardware and software.…”
Section: Internet Of Things (Iot)mentioning
confidence: 99%
“…Figure 1.5: User data handling in IoT [9] It is evident that for a seamless functioning of the IoT framework, its three components, namelyhardware, software and supporting architecture layers must coordinate and function in synchronization with each other. This being said, current niche markets retailing smart devices for IoT environments pose one or many of the following challenges in order to ensure the robustness and integrity of a connected environment [10]:…”
Section: Softwarementioning
confidence: 99%
“…Because of the versatility of the QCA approach, the authors suggested that it can provide useful analytical tools for data in multi-modal monitoring. By explaining the role of actigraphs in personalized health, fitness monitoring and Internet of Medical Things (IoMT) paradigm, Athavale [26] presented a study utilizing wearable devices to capture and analyze physiological data at home-based health monitoring in an IoMT environment, and proposed a low level encoding scheme to improve actigraphy analysis. In order to ensure that there was no loss of information in encoding process, ML approach was used for the study validation.…”
Section: Summary Of Special Issue Papersmentioning
confidence: 99%
“…Similarly, traffic lights augmented with hyperspectral imaging and chem-bio sensors can be made locally smart when combined with weather sensors and the unique local population and infrastructure signatures. More concrete EC applications include scalable framework for early fire detection [99], disaster management services [100], accelerometers for structural health monitoring [101], micro-seismic monitoring platform for hydraulic fracture [102], a framework for searchable personal health records [75,76,103], smart health monitoring [76,104] and healthcare framework [105], improved multimedia traffic [106], a field-programmable gate array (FPGA)-based system for cyber-physical systems [107] and for space applications [108], biomedical wearables for IoMT [73,76,109], air pollution monitoring systems [110], precision agriculture [111,112], diabetes [74] and ECG [109] devices, and marine sensor networks [113].…”
Section: Edge Computingmentioning
confidence: 99%